2015
DOI: 10.1155/2015/926874
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Epstein-Barr Virus Reactivation in an Acquired Aplastic Anemia Patient Treated with Rabbit Antithymocyte Globulin and Cyclosporine A

Abstract: Epstein-Barr virus (EBV) associated lymphoproliferative disorder (LPD) after immunosuppressive therapy for aplastic anemia (AA) is extremely rare in a nontransplant setting and has not been well described. This report describes a severe AA patient in whom fatal EBV-LPD developed after being treated with rabbit antithymocyte globulins (ATG) and cyclosporine A (CsA). An 81-year-old man was diagnosed as having severe AA. He was started on CsA followed by administration of ATG for five consecutive days. One month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…Our study showed rare, but evident, cases of CMV‐ or EBV‐related disease, even though Sheinberg et al concluded that there is no need to routinely monitor EBV or CMV reactivation based on the absence of cases of CMV‐ or EBV‐related disease, except for subclinical viral reactivation in their cohort. A series of case reports of CMV‐ or EBV‐related disease following rATG‐CsA supports our observation . The cohort in the study by Scheinberg et al included a relatively small number of patients (n = 14) treated with rATG‐CsA and mainly included patients receiving IST with horse ATG (n = 59).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our study showed rare, but evident, cases of CMV‐ or EBV‐related disease, even though Sheinberg et al concluded that there is no need to routinely monitor EBV or CMV reactivation based on the absence of cases of CMV‐ or EBV‐related disease, except for subclinical viral reactivation in their cohort. A series of case reports of CMV‐ or EBV‐related disease following rATG‐CsA supports our observation . The cohort in the study by Scheinberg et al included a relatively small number of patients (n = 14) treated with rATG‐CsA and mainly included patients receiving IST with horse ATG (n = 59).…”
Section: Discussionsupporting
confidence: 82%
“…All seven reported cases with EBV‐LD occurred after rabbit ATG, not horse ATG, although the ATG source and peak EBV load were not described for one case. Furthermore, among five case reports measuring EBV load using the same method as in the current study, the median EBV peak load was 6.6 log (range, 2.08‐6.9 log), which was higher than that of the respective cohort in the study by Sheinberg et al and the subsets without EBV‐LD in our study. Based on the current data, the findings of Sheinberg et al, and corroborating case reports from previous literature, higher CMV and EBV loads could be an important cue to raise clinicians' awareness of the potential risk for CMV‐ and EBV‐related diseases during periodic follow‐up in AA patients receiving rATG‐CsA.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations